Dynamics of pro-poor growth: an analysis of distributional pattern of growth in Pakistan (2007-2018) - Noor Fatima; Said, Rusmawati; Mazlan, Nur Syazwani; Mohamed Nor, Norashidah (Transnational Press London, 2024)
The study investigates the interconnection between economic growth, inequality, and poverty in Pakistan, focusing on pro-poor growth. Among other measures of pro-poor growth, study estimated “poverty equivalent growth rate” to quantify the distributional pattern of growth in Pakistan by using the HIES (Household Integrated Economic Survey) data, from 2007-08 to 2018-19 at national, regional and provincial levels. This is the only measure that adheres to most important axiom of monotonicity for reducing poverty; it evaluates both the magnitude of growth and the extent to which the impoverished population benefits from it. It is found that distributional pattern of growth is heterogeneous during different sub periods in Pakistan Generally, the poorer among the poor are getting less distributional benefits of growth throughout the period considered. To tackle this skewed distribution of growth, it is crucial to allocate sufficient public funds to lagging regions, especially in rural areas of Pakistan. Adequate measures should also be implemented to establish permanent social safety nets capable of safeguarding Pakistan's most vulnerable populations from economic downturns and catastrophic events.